2020
DOI: 10.1016/j.ijid.2020.02.044
|View full text |Cite
|
Sign up to set email alerts
|

Impact of augmented renal clearance on the pharmacokinetics of linezolid: Advantages of continuous infusion from a pharmacokinetic/pharmacodynamic perspective

Abstract: The aim of this study was to assess the influence of renal function, in particular the presence of augmented renal clearance (ARC), on the pharmacokinetics of linezolid in critically ill patients. The effect of continuous infusion on the probability of therapeutic success from a pharmacokinetic/pharmacodynamic (PK/PD) perspective was also evaluated. Methods: Seventeen patients received linezolid (600 mg every 12 h) as a 30-min infusion and 26 as a continuous infusion (50 mg/h). The PK parameters were calculate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
43
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(46 citation statements)
references
References 33 publications
2
43
1
Order By: Relevance
“…This was different from the previous studies on Caucasian patients, for the upper limits of the concentrations were not included in their PK/PD indexes. The patients with ARC were common in the ICU, a 24 h continuous infusion of a daily dose of 1200 mg or 1800 mg LNZ was recommended in a previous study [16]. In our study, 900 mg q12h could also achieve a similar clinical response.…”
Section: Discussionsupporting
confidence: 59%
See 2 more Smart Citations
“…This was different from the previous studies on Caucasian patients, for the upper limits of the concentrations were not included in their PK/PD indexes. The patients with ARC were common in the ICU, a 24 h continuous infusion of a daily dose of 1200 mg or 1800 mg LNZ was recommended in a previous study [16]. In our study, 900 mg q12h could also achieve a similar clinical response.…”
Section: Discussionsupporting
confidence: 59%
“…The standard dose ensured a relatively high probability of treatment success in patients with MIC ≤ 1 mg/L [16,31]. However, in patients with normal or residual renal function, the standard dose was insu cient, and 900 mg q8h provided a higher probability of treatment success without compromising the safety [16]. In the present study, 1800 mg/day (600 mg q8h) or 1200 mg/day continuous infusion resulted in C min within MIC of 10 mg/L.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, renal impairment and renal replacement therapy appear to be risk factors for this drug-related thrombocytopenia [ 58 , 59 ], suggesting that this concern may not be applicable to patients with ARC. Of note, a recent study observed that linezolid clearance was still exceptionally elevated in those with ARC and the investigators concluded that a continuous confusion at 75 mg/h would be necessary to remain at concentrations of 2 mg/L or above [ 60 ]. Thus, even for drugs with non-renal elimination pathways, dosing adjustments may still need to be made.…”
Section: Effects On Antibiotic Therapymentioning
confidence: 99%
“…ARC seems to have no effects on meropenem 2g × 3 even for CrCl values of up to 250 mL/min, according to a study by Tamatsukuri et al [ 95 ]. For linezolid, continuous infusion seems to allow higher probability of reaching an optimal PK/PD target than intermittent infusion [ 96 ].…”
Section: What Can Be Done For Icu Septic Patients In Order To Applmentioning
confidence: 99%